Kulturowe matryce semantyczne — wiersz macedoński w refleksie polskim i chorwackim - Miodyński, Lech (Przekłady Literatur Słowiańskich, 2011)
Semantic matrices of the cultures — Macedonian poem in Polish and Croatian reflection This article describes the ways of transformations of the cultural-semantic elements in parallel translations of the Macedonian poetry. Their comparison through the material of lyric from 1955—1977 period (along with wide annotation in the perspective of communicational theory of translation) depicts differences in the extent of equivalency — ensuing from divergence of both traditions of intercultural relations. Croatian translations show much higher accuracy, articulateness and economy of forms of expression, relying on common extensive corps of south Slavonic lexis, often phraseology. Polish translations on many levels use a compensation — especially archaic stylisation, language embellishing advanced to affectation has high frequency. In the first case dominant method is usually syntagmatic translation or reproduction of the plates (cliches), in the second — applying of the functional cultural equivalents and deriving from the romantic heritage.